Constitutional-Legal Mechanism for Ensuring the Citizens' Rights for Participation in Local State Administration in the Republic of Kazakhstan - NEMEREBAEVA, Aigerim M.; ERALIEVA, Zhazira D. (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
Since the declaration of the state independence of Kazakhstan, along with the implementation of systemic economic, political and social reforms, the state chose a policy of large-scale reforming the system of local state administration to maximize the implementation of the declared rights of citizens. The conducted research provided an opportunity to develop and reveal the essence, content and objective factors of development of the constitutional-legal mechanism for ensuring the citizens’ rights for participation in local state administration in the Republic of Kazakhstan as well as to analyze its conceptual-categorical apparatus. Based on the author's factor model, a number of tendencies of the development of the investigated constitutional law were determined, specific ways of its modernization and qualitative efficiency improvements of its functioning were proposed. Also, it is argued that the institutions of state power are obliged to contribute to the development of a unified Strategy for Reforming the System of Local State Government that should be based on a set of the norms of the Constitution of the Republic of Kazakhstan, international standards of human rights and anthropocentrism in the field of building an effective system of local state administration.